Barriers to interspecific hybridization between Vigna unguiculata and Vigna vexillata - Barone, A.; Giudice, A. del; Ng, N.Q. (1992)
Interspecific hybridization between Vigna unguiculata and V. vexillata always failed: no seed was obtained in both crossing directions. Two different barriers to crossability were found: a pre-zygotic barrier and a post-zygotic one. Many abnormalities were observed in pollen-tube development, which reduced the percentage of fertilization to 18–30%. Differences in the percentage of fertilization were detected between the two accessions of V. vexillata involved in the interspecific crosses. The development of the interspecific embryo was analyzed and the embryo and endosperm nuclei always degenerated 5–8 days after pollination. The growth of the embryo stopped at a globular stage, which is too early for excision and in vitro culturing.